PENGARUH VARIABEL PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, PERCEIVED ENJOYMENT DAN ATTITUDE TERHADAP PEMANFAATAN VISUAL HOTEL PROGRAM PADA HOTEL-HOTEL DI YOGYAKARTA - Latifah Latifah; Azka Nur Afifah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2013)
This research aimed for examining the influence of perceived usefulness, perceived ease of use, Perceived Enjoyment and attitude in using information technology. Attitude will influence particular behavior in using technology information showed by behavior intention. Thus study using questionnaire to collect data, and using purposive sampling technique to determine the respondents which is users who work at hotels in Jogjakarta that uses software VHP (Visual Hotel Program). 50 copies of questionnaire was distributed, with 72% response level, but only 36 copies ones were submitted for analysis. Analysis of data using alternative methods of PLS (Partial Least Square) supported by the Smart PLS application program. The analysis results Perceived Enjoyment has no significant influence toward attitude in using VHP software, perceived ease of use and perceived usefulness have significant influence toward attitude in using VHP software. Attitude has significant influence toward behavior intention in using VHP software.